2018
DOI: 10.21037/atm.2018.01.28
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive versus conventional spine surgery for vertebral metastases: a systematic review of the evidence

Abstract: One of the major determinants of surgical candidacy in patients with symptomatic spinal metastases is the ability of the patient to tolerate the procedure-associated morbidity. In other pathologies, minimally invasive (MIS) procedures have been suggested to have lower intra-operative morbidity while providing similar outcomes. We conducted a systematic review of the PubMed library searching for articles that directly compared the operative and post-operative outcomes of patients treated for symptomatic spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 81 publications
0
47
0
2
Order By: Relevance
“…In this study, 460 (79.31%) patients received palliative surgery including 290 posterior laminectomy, 155 subtotal corpectomy, and 15 subtotal corpectomy combined with microwave ablation and vertebroplasty. Most of them presented severe pain and spinal instability but the general conditions were good with KPS score more than 60 and Frankel score in D and E. The revised Tokuhashi score have suggested that surgery only be considered in patients with a life expectancy of more than 6 months, meaning that patients, especially those with aggressive primary tumor metastasis, are ineligible for surgical symptom palliation. However, in this multicenter case series, lung cancer was the most common metastasis, as seen in 198 patients.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this study, 460 (79.31%) patients received palliative surgery including 290 posterior laminectomy, 155 subtotal corpectomy, and 15 subtotal corpectomy combined with microwave ablation and vertebroplasty. Most of them presented severe pain and spinal instability but the general conditions were good with KPS score more than 60 and Frankel score in D and E. The revised Tokuhashi score have suggested that surgery only be considered in patients with a life expectancy of more than 6 months, meaning that patients, especially those with aggressive primary tumor metastasis, are ineligible for surgical symptom palliation. However, in this multicenter case series, lung cancer was the most common metastasis, as seen in 198 patients.…”
Section: Discussionmentioning
confidence: 84%
“…Unlike primary spinal tumors, the goal of surgery for spinal metastases is not cure but an overwhelming improvement of symptoms . That is to say, surgeons must consider the patients’ overall health, as well as the imaging examination of the vertebral metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews have compared minimal access surgery with open surgery in patients suffering from MSCC (7,8). Lu et al included six cohort studies (three prospective and three retrospective) representing a total of 252 patients (19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…W ith the developments of the social economy and medical technology, the survival time of cancer patients is significantly prolonged 1 . The spine is the most common bone metastasis site in cancer patients 2 . In the United States, more than one million cancer patients suffer from spinal metastasis each year, of which approximately 70% are in the thoracic vertebrae, 20% are lumbar vertebrae, and 10% are cervical vertebrae 3,4 .…”
Section: Introductionmentioning
confidence: 99%